Socialization of Anemia and Stunting Prevention For Adolescent Girls in Pegat Bukur Village, Berau District, Indonesia - Mulka, Sry Reski; Rahayu, Annisa Aulia; Octaviana, Denissa; Prastiwi, Dwi Indah; Elisabet, Meidiana Ines; Suryansyah, Muhammad; Utami, Najla Farijiah; Dafitri, Rayina Nova; Ardila, Rindi; Harahap, Siti Yusmialda; Dewi, Sri Rejeki Arta; Tonapa, Theo Piter; Windasari, W. (Golden Ratio of Community Services and Dedication, 2025)
The Community Service Program in order to carry out the Tri Dharma of Higher Education aims to encourage active involvement of students in the community and provide them with work experience in community development efforts. One of the implementation of KKN Batch 50 Year 2024 was carried out in Pegat Bukur Village, which is one of the villages in Sambaliung District, Berau Regency. One of the problems in Pegat Bukur Village is a health problem that is focused on handling stunting. One of the activities is the implementation of Socialization on the prevention of Anemia and Stunting along with making Infographics. Young women as future mothers need to prepare themselves to give birth to a quality generation. The need for nutritional knowledge about stunting and its prevention in adolescents is one way to reduce stunting rates in the future. The purpose of this activity is to increase the understanding of adolescent girls regarding anemia and stunting. The benefits of this activity are to carry out early prevention of the potential for anemia and stunting, by equipping adolescent girls as prospective mothers who are expected to give birth to healthy children and avoid stunting. The Anemia and Stunting Socialization also included the provision of blood supplement tablets to students of SMP Negeri 5 Kampung Pegat Bukur. This activity is a work program that can be attempted as a form of stunting prevention from as early as possible. From the results of data processing from pretest and posttest scores, it can be concluded that the socialization carried out is proven to increase the understanding of adolescent girls related to anemia and stunting. It is hoped that the service team can work with third parties who have legality in handling stunting so that the program implemented can have a deeper effect on the community.